The Contextual Character of Moral Integrity Transcultural Psychological Applications - Šamánková, Dita (Springer International Publishing, 2018)
"This book is a comprehensive and comprehensible coverage of the philosophical underpinning of the integrity construct as reflected in the Western literature-a must read for researchers and scholars interested in integrity assessments. The authors have integrated insights from several disciplines, and have written in a clear and engaging style. The Czech historical sketch gives an interesting background to these discussions." Professor Vish C. Viswesvaran, Florida International University, USA This book discusses outcomes of a study by the National Institute of Mental Health, Czech Republic, examining moral integrity in the post-communist Czech-speaking environment. Chapters map the history of the Euro-Atlantic ethical disciplines from moral philosophy and psychology to evolutionary neuroscience and socio-biology. The authors emphasize the biological and social conditionality of ethics and call for greater differentiation of both research and applied psychological standards in today's globalised world. Using a non-European ethical system - Theravada Buddhism - as a case study, the authors explore the differences in English and Czech interpretations of the religion. They analyse cognitive styles and language as central variables in formatting and interpreting moral values, with important consequences for cultural transferability of psychological instruments. This book will appeal to academics and other specialists in psychology, psychiatry, sociology and related fields, as well as to readers interested in the psychology of ethics. .